Pragmatic randomised controlled trial of an exercise programme to improve wellbeing outcomes in women with depression: findings from the qualitative component - Khalil, Elizabeth; Callaghan, Patrick; Carter, Tim; Morres, Ioannis (Scientific Research Publishing, 2012)
This paper reports the qualitative component from a pragmatic randomized controlled trial (PRCT), the quantitative component is reported in Callaghan, Khalil, Morres and Carter (2011). Exercise may be effective in treating depression, but trials testing its effect in depressed women are rare. Our previous research found that standard exercise programmes, prescribed by General Practitioners and based on national guidelines of intensity levels thought to produce health benefits, are not suitable for this group, as they find them discouraging and lonely, with many dropping out very early on. Exercise that is matched to participants’ preferred intensity improves mental health outcomes and attrition rates. Our aim was to develop such a programme. This study addressed the question: does mentored exercise of preferred intensity lead to better psychological, physiological and social wellbeing outcomes and improved adherence rates when compared with exercise of prescribed intensity in 38 depressed women? Focus groups were conducted with participants from both arms of the study, to explore their experience of the exercise programme and to gather information that might help to explain the quantitative outcomes, a technique recommended by previous researchers conducting pragmatic trials. Women in the experimental programme experienced a statistically significant improvement in their mood, physical health, sense of wellbeing, self-esteem and quality of life. They reported achieving these gains via a positive experience which encouraged continued attendance. In contrast, women who received the “exercise as usual” programme experienced no significant benefits, were less likely to continue attending, and markedly less enthusiastic.